Study of Retinal Nerve Fibre Layer Thickness in Type 2 Diabetes Mellitus by 3-Dimensional Optical Coherence Tomography from Eastern India - Rudrajit Paul, Asim Kumar Ghosh, Bijoy Chakraborty, Souvik Dan (Journal of Applied Pharmaceutical Science, 2014)
Three dimensional optical coherence tomography (OCT) is a novel technique to diagnose retinal disorders. In diabetes, loss of retinal neurons is said to be an early event. We did a small pilot study from Eastern India to find the usefulness of OCT in detecting changes in retinal nerve fibre layer (RNFL) in diabetics. We selected adult type 2 diabetics without overt retinopathy. Patients aged more than 60 or with pre-existing problems like glaucoma or vasculitis were excluded. RNFL thickness was measured using HRA-OCT Spectralis analyser. A 12º area around optic nerve head was analysed and depth of each quadrant was separately measured. The patient values were compared with normative Indian data to detect aberrations. Also, the venous blood sugar levels were measured and correlation studies were done with the retinal thickness values. Standard statistical methods were used. We had 10 diabetic cases (20 eyes) and 11 controls (22 eyes). There was significant thinning of RNFL in 6 (60%) diabetic cases and none of the controls. Two of the diabetics had severe thinning around optic nerve head. 83% of the patients had thinning on temporal side and 50% on nasal side. Mean blood glucose levels were higher in those with RNFL thinning. Both FBS and PPBS showed significant negative correlation with retinal thickness measurements. This is probably the first study of its kind from India. 3-D OCT can be a valuable tool in screening diabetics for complications. However, more studies are needed to better elucidate the role of this novel technology.
Keywords: OCT, Diabetes, retinal nerve fibre layer, optic nerve.